2022
DOI: 10.1111/scd.12705
|View full text |Cite
|
Sign up to set email alerts
|

Oral lesions and saliva alterations of COVID‐19 patients in an intensive care unit: A retrospective study

Abstract: Aim To detect the type and frequency of oral lesions and clinical conditions suggestive of saliva alterations in COVID‐19 patients in an intensive care unit (ICU), as well as to describe the patient´s management in each case Methods Information about oral conditions and mechanical ventilation was collected from oral medicine records of COVID‐19 patients in an ICU ( n = 519) Results From the total collected, 472 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
11

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 29 publications
5
25
0
11
Order By: Relevance
“…Still, this subject is under researched and further exploration is required. Finally, previous studies of ICU COVID-19 patients reported xerostomia, mucosal blistering and ulcers, rash, lip necrosis, and loss of taste and smell (Kamel et al, 2021;Eduardo et al, 2022;Yoshino et al, 2022). These can exacerbate such conditions as periodontitis, being an important risk factor for complications in patients with COVID-19 hospitalized in the ICU (Marouf et al, 2021).…”
Section: Gregorczykmentioning
confidence: 90%
“…Still, this subject is under researched and further exploration is required. Finally, previous studies of ICU COVID-19 patients reported xerostomia, mucosal blistering and ulcers, rash, lip necrosis, and loss of taste and smell (Kamel et al, 2021;Eduardo et al, 2022;Yoshino et al, 2022). These can exacerbate such conditions as periodontitis, being an important risk factor for complications in patients with COVID-19 hospitalized in the ICU (Marouf et al, 2021).…”
Section: Gregorczykmentioning
confidence: 90%
“…As a symptomatic therapy, artificial saliva is usable as a saliva substitute for patients with xerostomia, dry mouth, or hyposalivation. Eduardo et al [153] prescribed artificial saliva for dry mouth of COVID-19 patients in an intensive care unit. Unfortunately, they memtioned neither treatment procedure nor clinical outcome in detail.…”
Section: Substitution For Salivamentioning
confidence: 99%
“…Eduardo et al [153] prescribed artificial saliva for dry mouth of COVID-19 patients in an intensive care unit. Unfortunately, they memtioned neither treatment procedure nor clinical outcome in detail.…”
Section: Use Of Artificial Saliva and Outcomementioning
confidence: 99%